Nonlinear model for the instability detection in centerless grinding process - Robles-Ocampo, Jose Billerman (Strojniški vestnik, 2012)
In this work a novel nonlinear model for centerless grinding is presented. The model describes the dynamic behavior of the process. The model considers that the systems stiffness depends on the existence of lobes in the workpiece surface. Lobes geometry is treated as a polygonal shape and it is demonstrated that the system can be represented as a Duffings equation. It is shown that there is a critical lobe number, where the systems present an unstable behavior; the critical lobe number is identified through the geometric stability index. Instabilities in the centerless grinding process are analyzed with two methods: the phase diagram and the continuous wavelet transform. The presented results show that the dynamic behavior of the centerless grinding process can be represented with a cubic stiffness function that is obtained from the analysis of the surface topology.
Keywords: brušenje brez konic; drdranje; fazni diagram; indeks geometrijske stabilnosti; nekrožnost; nelinearni model